Etos Kerja Kepala Sekolah di SMA Quran Darul Fattah Kecamatan Rajabasa Kota Bandar Lampung - Agung Prayitno; Cipto Handoko; Muhammad Yasin (Journal of Islamic Education and Learning, 2023)
When doing a job, a person's style and motivation will show whether he works seriously or just pretends to. If you are responsible or not, etc. The views, expectations, and habits of the work group shape how a person lives and does their job. So, a person's work ethic can be changed by the work ethic of the group. The goal of this study was to find out how hard the principal of the Quran Darul Fattah High School in Bandar Lampung City's Rajabasa District works. This type of research is called "qualitative descriptive research." It is a method of research that produces descriptive data in the form of written or spoken words from the people and actors observed, directed from the background of the individual as a whole (holistic) without isolating individuals and their organizations in variables but looking at them as part of a whole. This study used different ways to collect data, such as interviews, observations, and written records. In this research, qualitative analysis is the method used to look at the data. Based on what was found in the analysis and discussion, the results of this study show that the work ethic of the Principal of SMA Quran Darul Fattah in the Rajabasa District of Bandar Lampung City is still getting better. It's clear from the improvements that have been made that the principal has worked hard, both in his own job and in trying to get his subordinates to improve. His discipline can be used as a model for improving the work ethic of the principal of Quran Darul Fattah High School in Rajabasa District, Bandar Lampung City. The work ethic of the principal of the Darul Fattah Quran High School in Rajabasa District, Bandar Lampung City keeps getting better, as shown by the indicators in the concept of a good work ethic. As a result, the principal's innovations at the Darul Fattah Quran High School in Rajabasa District, Bandar Lampung City have become a breakthrough that helps schools get better at competing globally. Because schools should be a good example of how to teach good character, especially if everyone in the school, especially the principal, has a good work ethic.